Report on Candidates' Work in the Secondary Education Certificate General and Basic Proficiency Examinations June 1989: Caribbean History - Caribbean Examinations Council (CXC, 1989)
This report contains general and detailed comments on the performance of candidates in the June 1989 Caribbean Secondary Education Certificate (CSEC) examinations in Caribbean History.
Keywords: CXC CSEC examinations